REKONSILIASI SAINS ISLAM: KONSEP, PRINSIP, DAN IMPLEMENTASI ILMUISASI ATAU PENGILMUAN ISLAM - Moh Maimun; Maskur Azka; Ahmad Mahali; Asnawan (Al Arsy: Journal of Education, Management and Islamic Thought, 2025)
This article examines the reconciliation of Islamic science by focusing on the concepts, principles, and implementation of the Islamization or scientification of Islam within the context of contemporary scholarship. The scope of the study covers the epistemological foundations of Islamic science, the relationship between revelation and reason, and the integration of Islamic knowledge with modern sciences. This study aims to elucidate the core concepts of Islamic science reconciliation, identify its underlying principles, and analyze practical forms of Islamization in the development of knowledge and education. The research employs a library research method using a philosophical and conceptual approach through critical analysis of works by contemporary Muslim thinkers and relevant academic literature. The findings indicate that the reconciliation of Islamic science is grounded in tawḥīd as the primary epistemological principle, the integration of revelation and rationality, and the orientation of knowledge toward human welfare. The implementation of Islamic scientification can be realized through the reformulation of scientific paradigms, educational curricula, and research practices infused with ethical and religious values. In conclusion, the reconciliation of Islamic science constitutes a strategic effort to establish a holistic and integrative scholarly tradition rooted in Islamic values while remaining responsive to modern scientific developments.